The occurrence of asthma in an extensive-stage small-cell lung cancer patient after combination therapy with atezolizumab and anlotinib: a case report - Deng, Wang; Chen, Juan; Deng, Xin-Yu (Frontiers in Immunology, 2024)
Background Extensive-stage small-cell lung cancer (ES-SCLC) is highly malignant, with early metastasis and high recurrence. Since therapeutic options are limited, ES-SCLC has a characteristically short survival period and extremely poor prognosis. A combination of immune checkpoint inhibitors (ICIs) and anti-angiogenic drugs can achieve promising efficacy and safety in patients with ES-SCLC as a second-line or subsequent treatment, extending survival to some extent. However, the clinical outcomes remain mostly unsatisfactory and are sometimes affected by treatment-related adverse events. Case presentation A 57-year-old woman with ES-SCLC was administered a combination therapy of atezolizumab (a PD-L1 inhibitor) and anlotinib [an oral multi-targeted tyrosine kinase inhibitor (TKI)]. She survived for 22 months, with no disease progression during the 28 courses of therapy. Unexpectedly, despite having no history of asthma, the patient developed asthma while receiving this regimen. This is possibly related to T-cell activation and the tumor immune microenvironment, which induce allergic inflammation after PD-L1 blockade. Conclusions This is the first report of an asthma-negative ES-SCLC patient who developed asthma after receiving atezolizumab plus anlotinib. Although this combination therapy may effectively extend survival in SCLC patients, asthmatic symptoms should be closely monitored.